Penerapan Metode Extreme Programming dalam Aplikasi E-Rapor Kurikulum 2013 Berbasis Web - Nurkholis Panji Saputra; Nur Rochmah Diyah Puji Astuti (STMIK Budi Darma, 2023)
This research aims to develop an e-Rapor application based on the 2013 Curriculum using the Extreme Programming (XP) method as a solution to address the issues in manually processing student grades with Microsoft Excel. The application is expected to assist teachers in managing student grades more quickly and efficiently while minimizing the potential for human errors. The selection of the XP method is based on its suitability for small to medium-sized development teams and its ability to adapt to rapid changes in requirements. The research findings indicate that the e-Rapor application was successfully implemented and tested using the black box testing method, achieving a 100% success rate. Further testing with the System Usability Scale (SUS) method yielded a score of 74.94, indicating that the application is well-received by users. The e-Rapor Curriculum 2013 Web-based application provides convenience to homeroom teachers and subject teachers in inputting grades, presenting data, and generating student grade reports. With the availability of this application, it is expected that the process of handling student grades will become more efficient and effective. The web-based nature of the application allows users to access student grade information online, anytime and anywhere